قضايا المرأة في فكر علي شريعتي من خلال كتابه مسؤولية المرأة - باسي, سهير; فقير, عبير (University of eloued جامعة الوادي, 2021)
"تناولت هذه الدراسة موضوع : قضايا المرأة في فكر علي شريعتي من خلال كتابه مسؤولية المرأة وقد تضمنت الدراسة ترجمة للمؤلف ،ومؤهلاته العلمية وقضايا المرأة في المجتمع الاسلامي والغربي . كما بنيت الدراسة جملة المفاهيم تتعلق بالموضوع ، وسلطة الضو على القضايا المرأة لدكتور علي شريعتي ،وطرق تناوله لمختلف القضايا وموقفه منها ."This study dealt with the topic: Women's Issues in the Thought of Ali Shariati through his book The Responsibility of Women. The study included a translation of the author, his academic qualifications and women's issues in Islamic and Western society. The study also built a set of concepts related to the subject, the authority of light on women's issues by Dr. Ali Shariati, the methods of dealing with various issues and his position on them.
دعوة
Keywords: قضايا المرأة _ فكرعلي شريعتي _مسؤولية المرأة _ حقوق المرأة _ البرجوازية _ الاستعمار الغربي _الحجاب وزي الشرعي _ الفرويدية; Women's issues - think Ali Shariati - women's responsibility - women's rights - the bourgeoisie - Western colonialism - the veil and the dress of law - Freudian